The cell cycle time of CD8+ T cells responding in vivo is controlled by the type of antigenic stimulus. - Heesik Yoon; Taeg S Kim; Thomas J Braciale (PLoS ONE)
A hallmark of cells comprising the mammalian adaptive immune system is the requirement for these rare naïve T (and B) lymphocytes directed to a specific microorganism to undergo proliferative expansion upon first encounter with this antigen. In the case of naïve CD8(+) T cells the ability of these rare quiescent lymphocytes to rapidly activate and expand into effector T cells in numbers sufficient to control viral and certain bacterial infections can be essential for survival. In this report we examined the activation, cell cycle time and initial proliferative response of naïve murine CD8(+) T cells responding in vivo to Influenza and Vaccinia virus infection or vaccination with viral antigens. Remarkably, we observed that CD8(+) T cells could divide and proliferate with an initial cell division time of as short as 2 hours. The initial cell cycle time of responding CD8(+) T cells is not fixed but is controlled by the antigenic stimulus provided by the APC in vivo. Initial cell cycle time influences the rate of T cell expansion and the numbers of effector T cells subsequently accumulating at the site of infection. The T cell cycle time varies with duration of the G(1) phase of the cell cycle. The duration of G(1) is inversely correlated with the phosphorylation state of the retinoblastoma (Rb) protein in the responding T cells. The implication of these findings for the development of adaptive immune responses and the regulation of cell cycle in higher eukaryotic cells is discussed.